Comparison of two different techniques for complex image matching - 437293 Muhammad Faisal Zafar; Dzulkifli Mohamad; International Arab Conference on Information Technology (2002 : University of Qatar, Doha, Qatar) (Skudai : Universiti Teknologi Malaysia, 2002)
40